2020
DOI: 10.1364/ol.409749
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient double plasma mirror producing ultrahigh-contrast multi-petawatt laser pulses

Abstract: We present a highly efficient double plasma mirror (DPM) that provides ultrahigh-contrast multi-petawatt (PW) laser pulses with a temporal contrast ratio reaching 1 0 17 up to 160 ps and 1 0 12 up to 2 ps before the main pulse. The high reflectivity of 70%, along with the high-contrast enhancement factor of  700,000, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…A plasma mirror is utilized to enhance the contrast ratio after pulse compression, where weak prepulses pass through an anti-reflection window glass, while the main femtosecond pulse is reflected by the plasma generated by the leading edge of the main pulse. Choi et al reported that the contrast ratio of a multi-PW laser reached 10 −17 up to 160 ps and 10 −12 up to 2 ps before the main pulse by using a double plasma mirror system, which enabled irradiation of tens-ofnanometers-thick polymer targets at an intensity of about 10 22 W/cm 2 [45].…”
Section: Temporal Contrastmentioning
confidence: 99%
See 1 more Smart Citation
“…A plasma mirror is utilized to enhance the contrast ratio after pulse compression, where weak prepulses pass through an anti-reflection window glass, while the main femtosecond pulse is reflected by the plasma generated by the leading edge of the main pulse. Choi et al reported that the contrast ratio of a multi-PW laser reached 10 −17 up to 160 ps and 10 −12 up to 2 ps before the main pulse by using a double plasma mirror system, which enabled irradiation of tens-ofnanometers-thick polymer targets at an intensity of about 10 22 W/cm 2 [45].…”
Section: Temporal Contrastmentioning
confidence: 99%
“…Since such a target can be easily destroyed by a prepulse arriving before the main ultra-high intensity pulse, the contrast ratio between a prepulse and the main pulse must be extremely high. A plasma mirror has been shown to enhance the contrast ratio by attenuating prepulses and amplified spontaneous emission existing with a main ultra-high intensity laser pulse; the double plasma mirror system developed at CoReLS has been shown to produce a contrast ratio of the laser pulse as low as 10 −17 up to 160 ps and 10 −12 up to 2 ps before the main pulse [45], which has enabled the use of polymer targets as thin as 5 nm.…”
Section: Radiation Pressure Accelerationmentioning
confidence: 99%
“…This pedestal, the rising slope just before the main pulse, has a non-negligible effect on the plasma physics processes occurring on the target surface. Because it is also difficult to remove these pre-pulses and pedestal, we plan to suppress them by installing a plasma mirror in the future [23].…”
Section: Experimental Study Of the Coherent Contrastmentioning
confidence: 99%
“…Owing to the limitation of the available size and transverse parasitic oscillation in the Ti:sapphire gain media, femtosecond lasers based on optical parametric chirped-pulse amplifier (OPCPA) with a peak power of order 100 PW have been designed and are under construction [10,11]. The laser intensity will possibly exceed 10 23 W/cm 2 in the near future. With the development of ultra-high intensity femtosecond lasers, the investigations of electron acceleration, ion acceleration, x-/γ-ray generation, and astrophysical systems are being actively pursued.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation